The Effect of Trichoderma on The Growth and Yield of Red Chili Plants In Andisol - Vinny Pratiwi; Zaitun Ritaqwin Rita; M. Azizi; Hanim Rahayuani Ratnaningsih (SEAS (Sustainable Environment Agricultural Science), 2025)
Red pepper plants (Capsicum annum L.) are one of the most important horticultural commodities in Indonesia. One effort to increase the growth and yield of red pepper is by using biological soil fertilizers, namely Trichoderma, sp. Andisol is a type of soil with loose and fragile texture conditions, making this type of soil very easily carried away by rainwater, wind and landslides or experiencing erosion. This study aims to see the effect of Trichoderma sp on the growth and yield of red chili plants (Capsicum annum L.) on Andisol soil, which was carried out at the Experimental Garden of the Faculty of Agricultural and Animal Husbandry Sciences UNIKI and the UNIKI Faperta Laboratory, the study used a Randomized Block Design Factorial Pattern (RAK) 3 × 3 with 3 replications, so that it has 9 with a combination of treatments of 20 grams, 25 grams and 30 grams. The best growth of chili plants was found at a dose of 30 grams of Trichoderma and the best chili plant results were found at a Trichoderma dose of 25 grams.